Customer-Centric Marketing with AI and Data Science Integration in Developing Consumer Satisfaction-Based Marketing Strategies - Nugroho, Dony Ari (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The development of digital technology has encouraged companies to adopt customer-centric marketing strategies that focus on consumer satisfaction. The integration of Artificial Intelligence (AI) and Data Science opens up opportunities to improve data analysis accuracy, personalize experiences, and make real-time decisions. However, many companies still experience a gap between the potential of technology and the optimal implementation of strategies. This study aims to explore the effectiveness of integrating AI and Data Science into customer-centric marketing strategies based on customer satisfaction. A qualitative approach was used with participants including marketing managers, strategy teams, and active consumers. Data was collected through in-depth interviews, participatory observation, and document analysis, then analyzed using a thematic-inductive approach with triangulation of sources for validity. The research findings indicate that the integration of AI and Data Science enhances market segmentation accuracy, enriches customer experience through personalization, and strengthens real-time data-driven decision-making. There is a positive correlation between the use of this technology and increased consumer satisfaction. However, challenges include the need for strict data governance, skill gaps in human resources, and high initial investment requirements. The implications of this study emphasize the importance of developing technological capabilities and human resources to maximize the benefits of AI and data science in marketing strategies, while maintaining consumer trust and loyalty in a sustainable manner.